Experts in Communication and Fashion. Professional Quality in crisis time - Pérez Curiel, Concha (2013)
In the area of specialized news reporting, fashion occupies an increasingly role. The demand of the next media professional requires knowledge, deepening and practice to offset the presence of interested and intruder sources, which annul the role of the Fashion Journalist. This investigation is based on aspects like the lack of fashion specialized journalists formation, the lack of quality inside the journalistic texts and also the perspectives of new companies and work inside the Fashion Communication sector. The content analysis based on the VAP Tool (Value Added Journalism) that measures the quality of the information and also the making of personal interviews directed to specialized fashion sources that composes the methodological corpus of the investigation.